STRATEGY MANAGEMENT OF ‘KOPWAN’ AS AN ULTRA-MICRO FINANCE SOLUTION FROM ONLINE LOANS - Arodha, Dianidza (Mimbar Administrasi Mandiri, 2025)
Indonesia's Women's Cooperative (KOPWAN) plays a vital role in empowering women through ultra-micro financing solutions. However, KOPWAN faces significant sustainability challenges, particularly competition with unregistered online loans. While KOPWAN provides more affordable financing access and skill training programs, limitations in capital and a lack of technological understanding among members represent weaknesses that need to be addressed. Conversely, there are opportunities for collaboration with formal financial institutions and government support for cooperatives that can enhance KOPWAN's capacity. The threats posed by intense competition and the risk of loan defaults must also be considered. By leveraging existing strengths and opportunities while addressing weaknesses and threats, KOPWAN can continue to contribute to women's empowerment and improve economic welfare in Indonesia. This research aims to analyze the sustainability challenges faced by KOPWAN and provide strategic recommendations to enhance the effectiveness of women's empowerment programs in the future.